Vacuum ultraviolet photochemistry of sulfuric acid vapor: a combined experimental and theoretical study. Issue 4 (12th January 2022) - Zhang, Cuihong; Lin, Xiaoxiao; Tang, Xiaofeng; Fittschen, Christa; Hartweg, Sebastian; Garcia, Gustavo A.; Long, Bo; Zhang, Weijun; Nahon, Laurent
Abstract : VUV photoionization of gas-phase H2 SO4 has been studied by using i 2 PEPICO. Three electronic states of H2 SO4 + have been prepared and their ionization energies are determined, as well as the adiabatic appearance energy of fragments. Abstract : We present a vacuum ultraviolet (VUV) photoionization study of the gas-phase sulfuric acid (H2 SO4 ) molecule in the 11–14 eV energy range by using the method of synchrotron radiation-based double imaging photoelectron photoion coincidence (i 2 PEPICO) spectroscopy complemented with accurate theoretical calculations. The slow photoelectron spectrum (SPES) of H2 SO4 has been acquired and the three electronic states of H2 SO4 +, X 2 A, A 2 A and B 2 A have been populated and assigned. The adiabatic ionization energy of the H2 SO4 molecule towards the X 2 A cationic ground state is measured at 11.684 ± 0.006 eV, in accordance with high-level calculated findings. With increasing photon energies, the H2 SO4 + cation dissociates into HSO3 + and OH fragments and their adiabatic appearance energy is measured at 13.498 ± 0.007 eV. Then, the enthalpies of formation for the species involved in the photoionization and dissociative photoionization have been determined through a thermochemical cycle.